Membrane based dehumidification and evaporative cooling using wire mesh media - Goodnight, Jared R. (Kansas State University, 2011)
Membrane dehumidification and evaporative cooling applications have the potential to significantly improve the energy efficiency of air conditioning equipment. The use of wire mesh media in such membrane applications is feasible but has not been studied extensively. Therefore, the aim of this work is to investigate the heat and mass transfer performance of several different wire mesh media in membrane based dehumidification and evaporative cooling. There were six wire mesh membranes tested in an experimental facility. The wire mesh membranes vary with respect to percent open area, wire diameter, pore size and material. Two non-permeable, solid membranes were also tested in the facility and compared with the wire mesh membranes. The test section of the experimental facility consists of a narrow air duct and a plate apparatus. The membrane samples were fashioned into rectangular plates and installed into the test section. The plate membranes separate liquid water and air flow streams. The inlet air temperature and humidity are altered to produce condensation or evaporation at the membrane surface. The average convective heat and mass transfer coefficient of the air boundary layer is measured for each of the experimental plates. Membrane based dehumidification and evaporative cooling were accomplished using the wire mesh media. However, the wire mesh membranes did not exhibit any significant differences in their performance. The mesh plates were compared with the solid plate membranes and it was discovered that the solid plates exhibited significantly higher heat transfer coefficients during condensation conditions. This result most likely is due to the formation of large water droplets on the solid plates during condensation. The experimental data is then compared to analytical predictions of the heat and mass transfer coefficients developed from several heat transfer correlations and by invoking the heat and mass transfer analogy. The experimental data is also compared directly with the heat and mass transfer analogy. It was found that the data did not compare well with the heat and mass transfer analogy. This result is attributed to the fact that the membrane surface limits the amount of direct exposure to the gas-liquid interface.
Keywords: Membrane dehumidification; Membrane evaporative cooling; Surface tension elements; Combined heat and mass transfer; Wire mesh; Condensation; Engineering (0537); Environmental Engineering (0775); Mechanical Engineering (0548)